Greek medicine in ancient times and its ophthalmological aspects - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The article presents the state of medical knowledge in ancient Greece. Sacred medicine related to the cult of Asclepius and the origin of secular medicine is described. Ophthalmological aspects concerning the anatomy of the eye, diagnosis and treatment of ocular diseases are emphasized.